Possidius of Calama a study of the North African episcopate at the time of Augustine - Hermanowicz, Erika T.; Oxford eBooks (Oxford : Oxford University Press, 2008)
Hermanowicz analyzes Possidius' episcopal career and the biography of his life-long friend St. Augustine, the Vita Augustini. She challenges the widely-held view of Augustine dominating the theological landscape of North Africa demonstrating how often his position was isolated on key matters of law, coercion and diplomacy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Possidius, -- Saint, -- active 370-437.; Augustine, -- Saint, Bishop of Hippo; Christian saints -- Africa, North -- Biography; Roman law; Electronic books